2013
DOI: 10.1007/s00586-013-2765-x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with wound complications after surgery for sacral tumors

Abstract: Purpose The aim of this article is to summarize our experience in treating sacral wound complications after sacrectomy. We focus, in particular, on factors associated with wound complications, including surgical site infection (SSI) and wound dehiscence. Methods The definition of SSI devised by Horgan et al. was applied. Wound dehiscence was defined as a wound showing breakdown in the absence of clinical signs meeting the diagnostic standard for SSI. Between September 1997 and August 2009, 387 patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 25 publications
1
26
1
1
Order By: Relevance
“…Comparing the 4 patients who had lumbopelvic reconstruction and the 12 patients without reconstruction, the infection rate was higher in the first group (75%) than in the latter group (33%). Recently, Li et al have published a large series of sacral resections and analyzed the factors associated with wound complications 95 . Of the 387 patients 274 healed uneventfully, and 113 (29.2 %) had wound infection or dehiscence.…”
Section: Outcomementioning
confidence: 99%
“…Comparing the 4 patients who had lumbopelvic reconstruction and the 12 patients without reconstruction, the infection rate was higher in the first group (75%) than in the latter group (33%). Recently, Li et al have published a large series of sacral resections and analyzed the factors associated with wound complications 95 . Of the 387 patients 274 healed uneventfully, and 113 (29.2 %) had wound infection or dehiscence.…”
Section: Outcomementioning
confidence: 99%
“…Li et al reported that preoperative radiotherapy is an independent risk factor for wound complications after surgery for sacral tumors and suggested that late vascular changes after radiotherapy may adversely affect wound healing [17, 2931]. We saw a strong correlation between surgical complications and the implementation of surgery combined with preoperative radiotherapy (Table 7; Pearson’s chi-square test, p = 0.006).…”
Section: Discussionmentioning
confidence: 52%
“…In our study, 11 and 7 patients (total 29.5%) in the preoperative radiotherapy group developed complications of chronic radiation enteritis and cystitis, respectively. Li et al [29] demonstrated that the specific method applied to reduce intraoperative blood loss (135 of 183 patients underwent ABO) was a risk factor for wound complications in univariate analysis but was not significant in multivariate analysis. We found no correlation in our study between the application of ABO and complications (Pearson’s chi-square test, p = 0.113).…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of wound complications after sacrectomy is between 14.7% and 39% 8,22,31,36,46 (Table 3). In 2003, Zileli et al presented the results of 34 patients who underwent sacrectomy and reported a wound complication rate of 14.7%.…”
Section: Discussionmentioning
confidence: 99%
“…46 In 2013, Li et al presented a study of 387 patients who underwent sacrectomy and reported a wound complication rate of 29.2%. 22 Many factors influence this rate, including previous lumbosacral surgery, number of surgeons scrubbed in, low albumin level, type of surgery, prolonged operation time, older age (> 40 years), diabetes mellitus, previous radiation therapy, large tumor size, rectum rupture, CSF leakage, wide surgical exposure, proximity of the anus, presence of a huge dead space after sacrectomy, poor blood supply to the skin flap, and the use of instrumentation. 8,9,22,31,36,42,46 For patients undergoing total sacrectomy, the wound complication rate would be higher due to a longer operation time, wider surgical exposure, and larger tumor size.…”
Section: Discussionmentioning
confidence: 99%